Copy number variation of ZNF280BY in Bos taurus and Bos indicus breeds - C, JEEVAN; Ganguly, Indrajit; Deswal, Siddharth; Singh, Sanjeev; Dixit, S P (Indian Journal of Dairy Science, 2019)
The transcriptomic analysis has revealed abundant multi copy gene families on MSY region of the bovine Y chromosome. Previous studies indicated copy number variations (CNVs) of several genes were related to bull fertility. However, the copy number analysis of Y specific genes in Bos indicus breeds has not been investigated. Recent studies divulged that copy number of ZNF280BY gene ranged between 28 to 380 in Bos taurus bulls. We investigated the CNVs of ZNF280BY in a total of 69 bulls including four Bos indicus breeds and two Bos taurus by using relative Real time PCR. The single copy gene SRY was used as a reference to calculate the multi copy gene, ZNF280BY. All breeds showed significant variation in the copy number among individual members. The copy number was found to be ranging from 124 to 591 with median copy number 301. Ongole breed had higher levels (Median copy number = 388) while Gir in lower levels (Median copy number = 263) than other breeds. This study provide the range of copy number of ZNF280BY which need to further evaluated for their association with the fertility traits in Bos indicus.